Pacing pattern and performance during the 2008 Olympic rowing regatta - Muehlbauer, T.; Schindler, C.; Widmer, A. (European Journal of Sport Science, 2010)
Data from the 2008 Olympic rowing regatta were analysed to determine the time distribution during races and to assess whether pacing patterns differ between heats and the corresponding finals. Absolute and relative sector times for all of the four 500 m race quarters were analysed, for all boats in all heavyweight heats and final races (n=72 boats for men, n=60 boats for women). Irrespective of race type, boat rank or boat type, analyses of variance with repeated measures revealed that absolute times in the second and/or third race quarter(s) were significantly (both sexes: P<0.001) longer than those either in the first or final quarter, resulting in a parabolic-shaped profile. Compared with the heats, the pacing pattern adopted during the finals was significantly different (females: P<0.013; males: P<0.001); that is, relatively slower in the first and second race quarter but relatively faster in the last quarter. The parabolic-shaped race profile indicates an anticipatory control of speed and energy distribution over the course of the 2000-m race. The observed changes in pacing pattern suggest that during the finals a more conservative starting pace is used, which could be physiologically advantageous, because some energy is withheld for the final spurt.